"Криминальная революция" как социетальный фактор - Рущенко, И. (Социология: теория, методы, маркетинг, 2008)
This paper presents an attempt to interpret theoretically the wide spread criminalization of social relationships evolving since the Soviet Union’s collapse in the 1990s. To a certain extent, criminal revolution is a spontaneous process caused by deep and grave crisis enveloping both the state and the society. A radical alteration of the existing social order, as well as a wide-ranging transformation of social relationships based on criminal ideas, practices, and interactions constitute the essence of this process. It was an inevitable consequence of all the cir cum stances in the early and middle 1990s: (1) permanent and circulating capital of the state-owned enterprises being privatized as a great profit potential and so as a real attraction for the criminals; (2) a weak state, in efficiency in law enforcement, and half-paralyzed police structures; (3) a vast impoverished population being forced to struggle for survival and for that reason ready to embark on any shady enterprises; (4) new generations of brave and daring criminals. How ever, the criminal revolution played a role of social catalyst that facilitated the emergence and rapid development of capitalist economic relations, gave rise to an “effective” owner, and even enhanced the social integration. A new historic challenge for Ukraine is to over come criminal practices and to trans form a now a days social order in our society into the new one, similar to accepted and legitimated in most European countries.